1988
DOI: 10.1038/sc.1988.39
|View full text |Cite
|
Sign up to set email alerts
|

Early prognostic factors for walking in spinal cord injuries

Abstract: SutntnaryThe authors present a prospective analysis with 1 year follow-up of about 157 consecutive spinal cord injured patients admitted to the Bordeaux CHU, over a 3 year period (1982)(1983)(1984)(1985). They present a method of analysing the walking status recovery in patients with spinal cord injuries from the early factors recorded on initial clinical examination. Twenty eight per cent of all patients are 'functional walkers', 1 year after injury. Three early factors were selected: age; the level of injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Also, we found no rela tionship between the initial level injury and recovery of ambulation. This finding is consistent with Deverat et al 4 Previous studies by Crozier et al noted a statistically significant improvement in prognosis for ambulation in Frankel B patients who had sparing of pin sensation below the zone of injury within 72 hours post SCI. 1 2 However in the present study no subjects (FA or NA) had the complete absence of pin sensation and therefore this factor could not be analyzed in relation to ambulation.…”
Section: Discussionsupporting
confidence: 91%
“…Also, we found no rela tionship between the initial level injury and recovery of ambulation. This finding is consistent with Deverat et al 4 Previous studies by Crozier et al noted a statistically significant improvement in prognosis for ambulation in Frankel B patients who had sparing of pin sensation below the zone of injury within 72 hours post SCI. 1 2 However in the present study no subjects (FA or NA) had the complete absence of pin sensation and therefore this factor could not be analyzed in relation to ambulation.…”
Section: Discussionsupporting
confidence: 91%
“…22 Kay et al found that being older than 50 had a significant negative effect on walking for AIS D subjects, while it was not a factor for AIS C subjects. 21 Although we expected those in higher age groups to be less likely to walk, we did not find an effect of age on walking after controlling for level and completeness of injury.…”
Section: Walkingmentioning
confidence: 99%
“…A broad range of different factors such as neurological deficit, age, gender, and electrophysiological measurements have been shown in previous studies to be closely related to functional outcome and, in particular, to walking ability after SCI (Burns et al, 1997;Crozier et al, 1991;Curt and Dietz, 1999;Daverat et al, 1988;Jacobs et al, 1995;Kay et al, 2007;Scivoletto et al, 2003;Sipski et al, 2004;Waters, 1996). The general characteristics of our patients, such as neurological level of injury, type of injury, or gender (predominantly men), were similar to these studies, although the mean age of 47.3 years in this study was slightly higher.…”
Section: Outcome Prediction In Motor Incomplete Spinal Cord Injurymentioning
confidence: 99%